Three new species of Fallacia from intertidal sediments in Japan. Issue 2 (3rd April 2019) - Li, Yuhang; Suzuki, Hidekazu; Nagumo, Tamotsu; Tanaka, Jiro; Sun, Zhongmin; Xu, Kuidong
Abstract : Three new species of Fallacia, F. miyajimensis sp. nov., F. nodulifera sp. nov., and F. similigemmifera sp. nov. are described from intertidal sediments in Japan. Their morphologies are studied with light, scanning and transmission electron microscopy. Fallacia miyajimensis differs from congeners in the presence of an apical pore, a finely porous conopeum possessing finger-shaped extensions with uniseriate rows of pores and a thick layer adjacent to the raphe with isolated depressions with small pores inside. Fallacia nodulifera differs from congeners in the presence of a unique asymmetric internal central nodule. It can also be distinguished by the combination of stria density, conopeum with short extensions, and centrally convex lateral sterna. Fallacia similigemmifera differs from congeners by its lanceolate valve outline, more or less straight, distinct lateral areas and the presence of a rectelevatum on internal central nodule. We suggest that the structural combination of the structure of the conopeum and the lateral sterna is a stable feature in species discrimination and could be used to define species groups. The cingulum of F . similigemmifera comprises a wide open valvocopula and two linear bands with different ligulae. This type of cingulum structure is also present in F. tenera, F. hodgeana, and probably in F. litoricola and F. fracta as well, and likely occurs commonly in Fallacia .